Magnetic Second-Harmonic Generation Of An Antiferromagnetic Film. - Lim, Siew Choo (Optical Society ofAmerica, 2002)

(untitled)
Second-harmonic generation of an antiferromagnetic film in Voigt geometry is calculated and analyzed. This calculation is carried out with an assumption of weak nonlinearity in a two-sublattice antiferromagnetic system. Second-harmonic waves are analyzed by the conventional approach of ordinary nonlinear optics.